The effects of different set configurations on concentric velocities in the barbell back squat - Wong, H. (Electronic Theses and Dissertations, 2020)
The purpose of this study was to determine if concentric velocities of lighter loads of could be augmented if they are performed heavier working sets. Twelve trained males with experience in the barbell back squat performed a 5RM and completed two separate squat training session conditions that consisted of three sets of five repetitions with 85% of their 5RM. Both conditions differed in the placement of a reduced-load set that was either performed after the working sets or during the warm-up period. No significant differences were observed in the working set MCVs in both conditions. Additionally, no significant differences were observed amongst MCVs in the Down Set and equivalent warm-up set loads. The results of this study suggest that postactivation potentiation may not occur using a similar set-load scheme.